Pertumbuhan Bibit Pinang Betara (Areca catechu L. Var. Betara) di Polybag dengan Aplikasi Kieserit - Nasamsir, Nasamsir; Hayata, Hayata; Febryanti, Latipa Reza (Universitas Batanghari, 2025)
Areca nut is a primadonna of Indonesian plantations, including Jambi. Before cultivating areca nut in the field, it is necessary to improve the planting medium, especially ultisol. This study was to test the application of kieserit on the growth of areca nut seedlings in polybags. The study was conducted on Pattimura Street, RT. 04, Simpang Rimbo Village, Alam Barajo District, Jambi City from April to June 2025. The materials used were 3-month-old areca nut seedlings, 3 kg polybags, nets, and NPK base fertilizer. The tools used included calipers, leaf color charts (LCC), cameras, meters, ovens, digital scales, and knives. The research design used was a completely randomized design (CRD) with different kieserit dosage treatments, each treatment was repeated three times so that there were 12 plots. The parameters observed were plant height, stem diameter, dry weight of the shoot, dry weight of the root, shoot-root ratio, seedling quality index, total leaf area, leaf color, and soil chemical analysis. The observation data were analyzed for variance followed by the DNMRT test at the 5% α level. The results showed that the application of kieserite significantly affected stem diameter, but did not significantly affect the dry weight of the shoot, dry weight of the root, the shoot-root ratio, the seedling quality index, the total leaf area, the leaf color, and the plant height of the areca nut seedlings. Application of kieserite at a dose of k4 (0.56 g) in 3 kg of planting medium increased stem diameter growth by 32.66% compared to k0.